Cyber Aggression di Kalangan Generasi Z Pengguna Instagram Ditinjau dari Self-Control dan Online Disinhibition - Bella Eka Siste Saputri; IGAA Noviekayati; Aliffia Ananta (JIWA: Jurnal Psikologi Indonesia, 2025)
Abstract Generation Z is a demographic highly active on social media platforms, particularly Instagram, where they express themselves and engage with others. However, improper use of these platforms can trigger cyber aggression behaviors. This study aims to explore the relationship between self-control and the online disinhibition effect on cyber aggression among Generation Z Instagram users in Surabaya. Using a quantitative correlational approach, the research involved 150 respondents aged 13 to 28, selected through purposive sampling. Data collection was conducted using psychological scales, and the results were analyzed with multiple linear regression. The findings reveal that self-control and the online disinhibition effect simultaneously have a significant influence on cyber aggression behavior. Individually, self-control negatively correlates with online aggression, meaning higher self-control reduces such behavior, while the online disinhibition effect shows a positive correlation, indicating that reduced online inhibitions increase cyber aggression. These results highlight the crucial need to strengthen self-control and digital awareness as effective strategies to prevent aggressive behaviors in the virtual space. Keywords: Cyber aggression, Generation Z, Instagram, Self-control, Online disinhibition effect Abstrak Generasi Z ialah kelompok usia yang aktif menggunakan media sosial, khususnya Instagram, sebagai sarana berekspresi serta juga berinteraksi. Namun, penggunaan yang tidak bijak dapatlah memicu perilaku cyber aggression. Temuan ini bertujuan untuk mengetahui hubungan antara self-control serta juga online disinhibition effect terhadap perilaku cyber aggression pada pengguna Instagram dari kalangan Generasi Z di Surabaya. Pendekatan kuantitatif korelasional digunakan dengan melibatkan 150 responden berusia 13–28 tahun, dipilih melalui teknik purposive sampling. Pengumpulan data dilakukan menggunakan skala psikologis serta juga dianalisis dengan regresi linier berganda. Hasil temuan membuktikkan bahwasanya self-control serta juga online disinhibition effect secara simultan memiliki hubungan signifikan terhadap perilaku cyber aggression. Secara parsial, self-control berhubungan negatif, sedangkan online disinhibition effect berhubungan positif terhadap agresi daring. Temuan ini menekankan pentingnya penguatan kontrol diri serta juga kesadaran digital didalam mencegah agresi di ruang maya. Kata kunci: Cyber aggression, Generasi Z, Instagram, Self-control, Online disinhibition effect